Effectiveness of therapeutic patient education interventions for chronic diseases: A systematic review and meta-analyses of randomized controlled trials - Correia, Jorge César; Waqas, Ahmed; Assal, Jean-Philippe; Davies, Melanie J.; Somers, Florence; Golay, Alain; Pataky, Zoltan (Frontiers in Medicine, 2023)
Chronic disorders are highly prevalent and are a major contributor to death and disability worldwide. Evidence has shown that therapeutic patient education (TPE) interventions are effective in improving a range of biomedical and psychological outcomes for a variety of chronic disorders. This has been demonstrated in scores of randomized controlled and evidence synthesis studies. However, no quantitative evidence has been published so far, on the content, and effective teaching strategies in TPE programs. The present systematic review and meta-analysis aims to bridge this gap, by answering the Who, What and How of TPE programs. Using a pretested search strategy, we searched Web of Science, MEDLINE, CINAHL, PsycINFO and COCHRANE database, from inception until August 2019. The search strategy was based on four comprehensive search concepts (patient education, chronic diseases, study design and outcomes). After a careful screening for eligible studies, two reviewers extracted qualitative and quantitative data from the randomized controlled trials on the TPE interventions. We also developed a taxonomy of curriculum skills and intervention delivery techniques to aid extraction of data in these domains. We found that these interventions were effective in improving biological outcomes (SMD= 0.48; 95% CI: 0.38 to 0.57), adherence to treatment regimen (SMD= 0.73; 95% CI: 0.46 to 1.002); knowledge (SMD= 1.22; 95% CI: 0.79 to 1.65); self-efficacy (SMD= 0.43; 95% CI: 0.30 to 0.56) and psychological health (SMD= -0.41; 95% CI: -0.53 to -0.29). This effectiveness was consistent across different delivery formats (individual, group and electronic) and delivery agents (non-specialists vs specialists). The flexibility in choice of mode of delivery and curriculum development gives stakeholders an opportunity for scale up of TPE interventions in healthcare settings.